Flexible Sensorless Position Control of Switched Reluctance Motors considering Both Embrace Design and Magnetic Saturation - Cai, Hui; Han, Yanjie; Jiang, Yujie; Luo, Zhaoxu; Liao, Jing Lin (Frontiers in Energy Research, 2022)
Precise estimation of position is essential in the control of switched reluctance motor (SRM). Traditionally, the intersection of the adjacent inductance can be utilized to estimate the rotor position, however, magnetic saturation brings about the variations of the intersection positon when the motor is operated at heavy load. To solve the problem, this paper develops a sensorless position estimation strategies considering the magnetic saturation and the embrace design. the sensorless control approaches can be chosen flexible according the characteristic of intersection. The rotor position estimation is achieved by employing six typical inductance positon without a requirement of additional positon sensor and other detection devices. By both simulation and experiment, the feasibility and validity of the proposed position estimation method is verified for the inertial operation, light load, heavy load, load mutation and high speed condition.